Naturalisation Immersion dans la fabrique des Suisse·sse·s - Kristol, Anne; Dahinden, Janine (Seismo, 2022)
Who decides what criteria are used to determine who can become Swiss? Which imaginaries of Swissness are mobilised in the context of naturalisation? Why is Swiss naturalisation policy so restrictive in international comparison? These questions are addressed in the exhibition Naturalisation, developed jointly by the Musée gruérien and the University of Neuchâtel. The exhibition examines the naturalisation procedure in the Gruyère region, and the symbolism associated with it, by combining reconstructions of the procedure with ethnographic and photographic documentation. It allows the public to live the experience of the candidates to naturalisation and to discover the point of view of the decision-makers, while being invited to take a reflective look at the naturalisation system put in place by the authorities. This book is the catalogue of the exhibition. In the first part, it proposes different framings and deepenings through essays by specialists from the social sciences, the museal area and photography. The second part presents the reflections discussed in the exhibition and a documentation of the naturalisation process in the form of images and ethnographic documents. Both documentary and reflective, this publication is a scientific and artistic contribution to the societal debate on naturalisation and the place given to diversity in Switzerland.